Efektifitas Metode Active Learning Berbasis Problem Solving Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Madrasah Aliyah - Taufiqurrahman; Mohammad Muchlis Solicin; Taqiuddin; Norsiyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study departs from the need for a learning model that is able to improve high-level thinking skills in the modern era, where Madrasah Aliyah students tend to still be oriented towards memorization and exam results. This study is intended to examine the success rate of the Active Learning method based on problem-based in improving the critical thinking skills of Madrasah Aliyah students in Pamekasan Regency, in this study using a qualitative research method supported by quantitative data. through observation techniques, in-depth interviews, and documentation involving 25 informants including an educator, students and several principals in three Madrasah Aliyah for three months (July–September 2025). The research results state that the use of the Problem Solving-based active learning approach increases student active participation, strengthens analytical skills, and provides significant improvements to learning outcomes. With an average value before treatment (pre-test) of 58.4 increasing to 74.2 after treatment (post-test). In addition, teachers and principals assess that this method makes the teaching and learning process more collaborative, reflective, and full of meaning. The conclusion of the study confirms that the Problem Solving-based Active Learning method is effective in developing students' critical thinking skills and can be used as a good learning strategy option in Islamic high schools.